Kesadaran Wajib Pajak, Kondisi Keuangan Wajib Pajak, Kebijakan Relaksasi Pajak, dan Kepatuhan Wajib Pajak - Ristianti, Komang Ardhelia; Sari, Maria Mediatrix Ratna (E-Jurnal Akuntansi, 2024)
The purpose of this reserach is to determine the effect of taxpayer awareness, taxpayer financial condition, PKB whitening, and BBNKB exemption on motor vehicle taxpayer compliance in Gianyar Regency. The method of determining the sample using accidental sampling. 100 samples was calculated using slovin formula. Data collection was carried out through a survey method using a questionnaire. The analysis technique used multiply linier regression. The result indicate taxpayer awareness, taxpayer financial condition, PKB whitening, and BBNKB exemption have positife effect on motor vehicle taxpayer compilance in SAMSAT Office in Gianyar Regency. Keywords: Awareness; Financial Condition; PKB Whitening; BBNKB Exemption; Taxpayer Compliance